1993
DOI: 10.1016/0042-6989(93)90029-v
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the gradient direction of a luminance ramp

Abstract: We report on the extent to which human observers are able to indicate the gradient direction of a luminance ramp. In our experiment modulation depth ranged from 1 to 64% and field sizes subtended 0.5 to 47.5' of visual angle. Observers are not able to indicate the gradient direction for modulation depths below 6%. For values above this threshold, the angular standard deviation in the responses decreases proportionally with the logarithm of the modulation depth and is about 11' for a modulation depth of 64%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, we acknowledge that these are different tasks. A similar error of T6 deg was found when observers were asked to judge the gradient direction, but only when the luminance contrast (measured as the standard Michelson contrast) was 64% (Erens et al, 1993a). By this measure of luminance contrast, our reference scene had a luminance contrast of 2.2% and a 1.5% contrast difference yielded reliable discrimination.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, we acknowledge that these are different tasks. A similar error of T6 deg was found when observers were asked to judge the gradient direction, but only when the luminance contrast (measured as the standard Michelson contrast) was 64% (Erens et al, 1993a). By this measure of luminance contrast, our reference scene had a luminance contrast of 2.2% and a 1.5% contrast difference yielded reliable discrimination.…”
Section: Discussionmentioning
confidence: 69%
“…For example, brightness discrimination ability does not predict but is superior to depth discrimination (Langer & Bülthoff, 2000). For luminance gradients, it has been found that both detection (Bijl, Koenderink, & Toet, 1989;McCann, Savoy, Hall, & Scarpetti, 1974) and the ability to determine gradient direction (Erens, Kappers, & Koenderink, 1993a) depend on within-image contrast and not on field size. Other studies (Curran & Johnston, 1996;Todd & Mingolla, 1983) suggest that small changes in gradients influence the human visual system's interpretation of shape even when other sources provide parallel or conflicting information.…”
Section: Introductionmentioning
confidence: 97%
“…Appendix, we might expect the local solid shape to bemore accurately determined at the attached shadow boundary. Erens Erens, Kappers and Koenderink, 1993a;Erens and de Haan, submitted showed that indeed, in regions of high contrast, observers perceive better the gradient direction and the curvature of the eld of isophotes.…”
Section: Attached Shadow Boundarymentioning
confidence: 99%
“…They are less sensitive to obliqueness, but in non-planar objects they are immediately aware of the obliqueness variations due to local surface attitude variations which cause modulations of texture contrast (not just shading). Human observers can use pure shading in the absence of texture as a shape cue, but they are dependent on complementary cues (e.g., contour) to deploy the shading cue effectively, 41 because of the large group of ambiguity transformations in the case the flow direction is not specified.…”
Section: D Textures -The Global Structure Of the Illuminance Flowmentioning
confidence: 99%